2012
DOI: 10.1021/jf301719k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enzymatic Deamidation of Soy Protein by Protein–Glutaminase on the Flavor-Binding Properties of the Protein under Aqueous Conditions

Abstract: The effect of the enzymatic deamidation by protein-glutaminase (PG) on flavor-binding properties of soy protein isolate (SPI) under aqueous conditions was evaluated by a modified equilibrium dialysis (ultrafiltration) technique. Binding parameters, such as number of binding sites (n) and binding constants (K), were derived from Klotz plots. The partial deamidation of SPI by PG (43.7% degree of deamidation) decreased overall flavor-binding affinity (nK) at 25 °C for both vanillin and maltol by approximately 9- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 32 publications
1
30
1
2
Order By: Relevance
“…The lower overall binding of vanillin in DSM was expected because deamidation by PG reduces the number of available amide groups by converting most of glutamine residues in soy protein to glutamic acids. Therefore, the potential to form covalent bonds (Schiff bases) with the carbonyl group of vanillin was decreased (Suppavorasatit and Cadwallader 2012). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The lower overall binding of vanillin in DSM was expected because deamidation by PG reduces the number of available amide groups by converting most of glutamine residues in soy protein to glutamic acids. Therefore, the potential to form covalent bonds (Schiff bases) with the carbonyl group of vanillin was decreased (Suppavorasatit and Cadwallader 2012). …”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with the results for odor detection thresholds. This could be explained in terms of flavor‐protein interactions in these 2 soymilks in that the deamidation by PG decreased the interactions between proteins in soymilk and carbonyl groups of the flavor compounds (Lozano 2009; Suppavorasatit and Cadwallader 2012). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reversible binding forms contain hydrogen bond and hydrophobic interaction, which play a primary role during the flavour substances absorbing process (Liu et al ., ; Zhou et al ., ). For example, studies have found that small aldehydes could bind to proteins by the irreversible covalent bond or hydrophobic interaction (Gianelli et al ., ; Suppavorasatit & Cadwallader, ). Herrera‐Jimenez et al .…”
Section: Introductionmentioning
confidence: 99%